2018
DOI: 10.1037/adb0000372
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of distress tolerance treatment for smoking cessation.

Abstract: We previously developed a distress tolerance (DT)-based treatment that showed promising results for smokers with a history of early lapse. In the current study, we conducted a randomized controlled trial of this DT treatment for a general population of smokers not limited to those with a history of early lapse. We randomized 116 participants (41% female) to DT or standard treatment (ST). Both treatments included 1 individual session during Week 1 followed by 7 group sessions during Weeks 2-9 (quit date at Sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 67 publications
(114 reference statements)
2
14
0
Order By: Relevance
“…Framing this intervention as a means of not only reducing nicotine dependence, but building distress tolerance ability, represents a potentially novel approach. Further, practice quit attempts are often an element of multi-component, DI-focused interventions for smoking cessation (e.g., Brown et al, 2018; Farris et al, 2016) and preliminary evidence shows that periods of brief withdrawal exposure prior to a quit attempt can promote smoking abstinence, increase latency to lapse, and prevent progression from first lapse to relapse (Hendricks et al, 2016; McCarthy, Bold, Minami, & Yeh, 2016). Examining the independent contribution of practice quit attempts to both increases in behavioral DT and downstream smoking cessation outcomes is an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Framing this intervention as a means of not only reducing nicotine dependence, but building distress tolerance ability, represents a potentially novel approach. Further, practice quit attempts are often an element of multi-component, DI-focused interventions for smoking cessation (e.g., Brown et al, 2018; Farris et al, 2016) and preliminary evidence shows that periods of brief withdrawal exposure prior to a quit attempt can promote smoking abstinence, increase latency to lapse, and prevent progression from first lapse to relapse (Hendricks et al, 2016; McCarthy, Bold, Minami, & Yeh, 2016). Examining the independent contribution of practice quit attempts to both increases in behavioral DT and downstream smoking cessation outcomes is an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Research should also continue to explore whether interventions designed to improve DT 51,52 can improve quit rates (although cf. 23 where DT vs. standard treatment did not improve quit rates). "Just-in-time" adaptive interventions delivered via mobile phones might help smokers with low DT to cope without lapsing by reminding them of ways to tolerate distress in the moment they need the help.…”
Section: Discussionmentioning
confidence: 98%
“…17 The ability to draw conclusions about the relations between DT and cessation success is limited in some studies because some of the studies predicting smoking outcomes have used small samples 18 and have been cross-sectional or retrospective rather than prospective. 22 Conversely, a recent randomized controlled trial 23 found that DT treatment in unselected smokers did not improve cessation rates relative to standard treatment, suggesting that perhaps DT is not causally related to cessation (or that the intervention did not increase DT enough to affect outcomes in a general population of smokers).…”
Section: Introductionmentioning
confidence: 98%
“…Second, as some evidence suggests that cannabis use may actually decrease distress tolerance and tolerance of pain administration (Amerongen et al, 2018;Naef et al, 2003), providing psychoeducation about the acute effects of cannabis on distress tolerance may be helpful for those who use cannabis to cope with negative affective or physical states may be beneficial. Third, given that distress tolerance can increase during treatment (Bornovalova, Gratz, Daughters, Hunt, & Lejuez, 2012;Brown et al, 2008;Brown et al, 2013;Cougle et al, 2011), clinicians may consider teaching patients with CUD skills to increase distress tolerance to improve cannabis-related outcomes.…”
Section: Discussionmentioning
confidence: 99%